Viral resistance to VRC01-like antibodies with mutations in loop D and V5 from an HIV-1 B′ subtype infected individual with broadly neutralization activity. (May 2022) - Zhang, Dai; Liu, Zhen; Wang, Wei; Chen, Ming-Xin; Hou, Jia-Li; Zhang, Zhen; Ren, Wei-Hong; Ren, Li; Hao, Yan-Ling
Abstract: Recently we identified the VRC01-like antibody DRVIA7(A7) from an HIV-1 B′ subtype-infected individual (DRVI01) with broad neutralization activity, and almost all viruses from the individual were resistant to both VRC01 and A7 lineage antibodies. Here, we identified and characterized a panel of HIV-1 variants with resistance to VRC01 and A7 using site-directed mutagenesis and swapping amino acid fragments of gp120. Site-directed mutagenesis revealed that E279D/R282K/N460A/T464N of gp120 from DRVI01 produced VRC01-susceptible variants. Multiple mutations significantly increased the neutralization sensitivity to VRC01. Residues N464 located at the tip of the V5 loop were considered irrelevant to the neutralization of VRC01. For DRVI01-derived viruses, the single N464T change fully produced VRC01-resistant variants; conversely, a single T464N mutation generated VRC01-susceptible variants. Alanine scanning revealed that the N464 residue plays a vital role in binding with VRC01. Neutralizing assays against A7 lineage antibodies showed that DRVI01-derived viruses with multiple mutations could be neutralized by A7 lineage antibodies with different neutralizing breadths. Combining the changes in loops D and V5 produced variants that were totally sensitive variants to A7 lineage antibodies. Highlights: We verified a few mutations in gp120 played a substantial role in neutralizing both VRC01 and A7 lineage antibodies. Primarily, we found that the residue N464 in the tip of the V5 region was a critical binding site of VRC01 and A7. Exploring the resistance mechanism against VRC01-class antibodies could reveal escaped ways of HIV-1 under immune pressure.